2022
DOI: 10.3390/nano12030493
|View full text |Cite
|
Sign up to set email alerts
|

Plumeria alba-Mediated Green Synthesis of Silver Nanoparticles Exhibits Antimicrobial Effect and Anti-Oncogenic Activity against Glioblastoma U118 MG Cancer Cell Line

Abstract: Plumeria alba (P. alba) is a small laticiferous tree with promising medicinal properties. Green synthesis of nanoparticles is eco-friendly, cost-effective, and non-hazardous compared to chemical and physical synthesis methods. Current research aiming to synthesize silver nanoparticles (AgNPs) from the leaf extract of P. alba (P- AgNPs) has described its physiochemical and pharmacological properties in recognition of its therapeutic potential as an anticancer and antimicrobial agent. These biogenic synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 60 publications
1
38
0
Order By: Relevance
“…On the other hand, based on inhibition zone assays, AgNPs (7–14 nm) synthesized using Thuja occidentalis leaf extracts were found to have inhibitory effect against S. aureus and E. coli at 40 µL of plant extract/nanoparticles, while leaf extracts were not effective [ 71 ]. By using AgNPs synthesized with extracts of Plumeria alba , it was found that they showed good antibacterial activity at concentrations of 25–100 µg/mL in terms of zone of inhibition, in which large zones of inhibition were observed mainly for Streptococcus pneumoniae (16 mm) at 100 µg/mL [ 72 ]. Similarly, other studies report obtaining AgNPs (approximately 15 nm in diameter) using waste material (dry grass), demonstrating activity against P. aeruginosa and Acinetobacter baumannii with a MIC = 3 µg/mL of AgNPs [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, based on inhibition zone assays, AgNPs (7–14 nm) synthesized using Thuja occidentalis leaf extracts were found to have inhibitory effect against S. aureus and E. coli at 40 µL of plant extract/nanoparticles, while leaf extracts were not effective [ 71 ]. By using AgNPs synthesized with extracts of Plumeria alba , it was found that they showed good antibacterial activity at concentrations of 25–100 µg/mL in terms of zone of inhibition, in which large zones of inhibition were observed mainly for Streptococcus pneumoniae (16 mm) at 100 µg/mL [ 72 ]. Similarly, other studies report obtaining AgNPs (approximately 15 nm in diameter) using waste material (dry grass), demonstrating activity against P. aeruginosa and Acinetobacter baumannii with a MIC = 3 µg/mL of AgNPs [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Figure-6 , the XRD pattern presents diffraction peaks at 27.90, 32.23, 46.29, and 54.91, corresponding to lattice plane values recorded at (111), (200), (220), and (311) of Ag crystals, respectively. The obtained peaks in the XRD pattern clearly explained that the Ag + ions had been completely reduced to Ag 0 by the reducing and stabilization compounds in the aqueous extract under reaction conditions [ 32 ]. There were some unassigned peaks in the chromatogram.…”
Section: Resultsmentioning
confidence: 99%
“…There were some unassigned peaks in the chromatogram. The presence of sharp peaks in the chromatogram indicated proteins or some bioorganic compounds in the NPs during synthesis [32]. Similar results of crystalline were reported by Rudrappa et al [32] on Plumeria alba-mediated AgNPs with XRD spectrum pattern that showed distinct diffraction peaks at 2θ angles of 38.19°, 44.37°, 64.77°, and 76.39°, indexed to the (111), ( 200), (220), and (311) Bragg's reflection of the face-centered cubic structure of Ag crystals, confirming their highly crystalline nature [32].…”
Section: Biosynthesis and Characterization Of Agnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main research directions to combat this problem has focused on the search for novel molecules that can complement or replace the antibiotics that are currently used and have lost their effectiveness over time 2 , 4 . A great number of these investigations explore secondary metabolites from fungi, plants, and animals for this purpose, sometimes using traditional medicine as a starting point to identify compounds of interest 5 7 .…”
Section: Introductionmentioning
confidence: 99%